Genomic analysis of NF-κB signaling pathway reveals its complexity in Crassostrea gigas. Issue 72 (January 2018) - Yu, Mingjia; Chen, Jianming; Bao, Yongbo; Li, Jun
Abstract: NF-κB signaling pathway is an evolutionarily conserved pathway that plays highly important roles in several developmental, cellular and immune response processes. With the recent release of the draft Pacific oyster ( Crassostra gigas ) genome sequence, we have sought to identify the various components of the NF-κB signaling pathway in these mollusks and investigate their gene structure. We further constructed phylogenetic trees to establish the evolutionary relationship of the oyster proteins with their homologues in vertebrates and invertebrates using BLASTX and neighbor-joining method. We report the presence of two classic NF-κB/Rel homologues in the pacific oyster namely Cgp100 and CgRel, which possess characteristic RHD domain and a consensus nuclear localization signal, similar to mammalian homologues and an additional CgRel-like protein, unique to C. gigas . Further, in addition to two classical IκB homologues, CgIκB1 and CgIκB2, we have identified three atypical IκB family members namely CgIκB3, CgIκB4 and CgBCL3 which lack the IκB degradation motif and consist of only one exon that might have arisen by retrotransposition from CgIκB1. Finally, we report the presence of three IKKs and one NEMO genes in oyster genome, named CgIKK1, CgIKK2, CgIKK3 and CgNEMO, respectively. While CgIKK1 and CgIKK3 domain structure is similar to their mammalian homologues, CgIKK2 was found to lack the HLH and NBD domains. Overall, the high conservation of the NF-κB/Rel, IκB and IKK family components in the pacific oyster and their structural similarity to the vertebrate and invertebrate homologues underline the functional importance of this pathway in regulation of critical cellular processes across species. Highlights: A complex NF-κB signaling component was identified in oysters. CgIκB gene expansion occurred by retrotransposition. CgIKK expansion occurred by adopting random duplication strategy.